Potensi Video Sebagai Media Edukasi Batik Keraton Yogyakarta - Novan Edo Pratama; Alvanov Zpalanzani; Imam Santosa (AKSA: Jurnal Desain Komunikasi Visual, 2020)
Yogyakarta Palace which is a source of culture in Yogyakarta iscurrently a cultural education tourism destination. By making thePalace as a source of cultural civilization, which is expected theculture will not eroded by the time just like the use of batik in thepalace. But, the reality that influences the rules and regulations forthe use of batik in the palace is not well understood by the people inYogyakarta at this time. For this reason, an educational video isneeded to preserve the batik campaign in the Yogyakarta Palace.One of the media that promotes effectively in the Batik Keratonsocial campaign is video. Because of its nature, one type of videowhich is a learning video is a type of video that presents visuallistening teaching material that can be used to preparemessages/subject matter such as culture Yogyakarta Batik Keraton.